Modern mathematics - West, Frank (Willford Press, 2018)
Mathematics plays a central role in our life. It studies themes like space, quantity, structure, etc. Mathematics is applied in various fields like engineering, finance, medicine, natural science and social sciences. Mathematics can be divided into two distinct branches namely, pure mathematics and applied mathematics. This book provides significant information of this discipline to help develop a good understanding of mathematics and related fields. This book, with its detailed analyses and data, will prove immensely beneficial to professionals and students involved in this area at various levels.